Water Quality Simulation of Reclaimed Water Supply Type Rivers and Application of Metal Organic Frameworks in Phosphorus Pollution Control - Qunbo QIAO; Mingxiang ZHANG; Bingyi HAN; Weihua WANG (Medžiagotyra, 2025)
This study focuses on the Xinfeng River, a regenerated water supply type river, and conducts water quality simulation and research on the application of metal organic framework materials (MOFs) in phosphorus pollution control. Using the storm water management model (SWMM) and environmental fluid dynamics code (EFDC) coupling model, the water quality changes of Xinfeng River under different scenarios of reclaimed water supply were simulated. The model was calibrated and verified through historical monitoring data, and the results showed that chemical oxygen demand (COD) could stably meet the Class V water quality standard, while NH3-N and total phosphorus (TP) could not meet the standard. Secondly, NH2-MIL-125(Ti) and NH2-UIO-66(Zr) were synthesized in this study. The morphology, structure, and properties of MOFs were characterized using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET), and thermogravimetric analysis (TGA), and they were used for adsorption and removal of phosphorus in water environments. The results indicate that NH2-MIL-125(Ti) has a larger adsorption capacity (10.42 mg/g), and the adsorption of phosphorus by NH2-MIL-125(Ti) and NH2-UIO-66(Zr) is more in line with the quasi second order kinetic model, and their adsorption isotherms are more in line with the Freundlich model. In addition, both adsorbents have good adsorption regeneration performance, with a phosphorus removal rate of over 85 % after 5 cycles. The water quality simulation model constructed in this study can accurately predict the impact of recycled water supply on river water quality. The selected MOFs materials have good phosphorus adsorption and removal performance, providing a scientific basis and technical support for improving water quality and controlling phosphorus pollution in recycled water supply rivers.